An experimental study of the effect adding locally manufactured shear studs on raising the punching of the flat slabs: دراسة تجريبية لأثر إضافة عناصر قص مصنعة محليا في رفع كفاءة البلاطات المسطحة على الثقب - Alaa Ali Saadat, Abd Alhamed Kikhea (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2020)
The slabs are one of the important structural elements in the buildings and constitute approximately 60% of the concrete size used. The flat slabs are an ideal solution that guarantees the speed and ease of implementation, especially in multi-storey buildings. The phenomenon of punching is a fundamental defect in these slabs, and the Syrian code addressed it to treat it in traditional ways such as making crowns for columns or falls of beams, which creates architectural and technological defects. The research includes conducting laboratory experiments on reinforced concrete slabs and analyzing the results with the aim of strengthening the flat slabs punching within the same thickness of the approved slab by linking the lower and upper reinforcement steel which provides a working principle similar to the trusses. The strength was made using shear studs (distribution case, matrix or diagonal), which in turn raised the efficiency of flat concrete slabs on the punching in terms of durability, deformations, and the breakdown mechanism in this case. The importance of the research lies in the use of locally manufactured elements within the workshop without the need for ready-made shear studs, which reflects positively on the cost and time of implementation.